Rekayasa Lalu Lintas Pada Kawasan Simpang Jl. Lingkar Tengah – Jl. DR. Leimena Di Kota Makassar - Mellyarti Mellyarti; Zulkifli Zulkifli (Journal of Applied Civil and Environmental Engineering, 2021)
Transportation problem, either in general or specifically in traffic, is a phenomenon occuring in human life. As the population of city increased, so does the traffic rate. If this is not followed by adequate improvement of transportation infrastructure, an imbalance might occur which will result in traffic jam. It can be seen particularly at Lingkar Tengah – Dr. Leimena road junction connecting Jalan Perintis Kemerdekaan - Dr Leimena road due to driver/rider against the direction. Data analysis and planning using method of road capacity manual (MKJI 1997) and the traffic modelling using PTV Vissim. Based on road performance analysis it is known that DS (degree of saturation) is 0.12 with service level ‗A‘ and average speed ≥23km/h with service level ‗D‘. From the calculation result, modelling is conducted using PTV Vissim modelling. Alternative for handling the intersection is using 2 methods, which are traffic light signaling for 3 phases with immediate straight at west corner and immediate left turning at east corner and bridge closure on Dr. Leimena road. Using PTV Vissim, the result is that intensity of travel time increases about 47.68% and 57.40% on the intersection.